Size Matters - 'Over'investments in a Relational Contracting Setting - Florian Englmaier; Matthias Fahn (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
The corporate finance literature documents that managers tend to over-invest in their companies. A number of theoretical contributions have aimed at explaining this stylized fact, most of them focusing on a fundamental agency problem between shareholders and managers. The present paper shows that over-investments are not necessarily the (negative) consequence of agency problems between shareholders and managers, but instead might be a second-best optimal response to address problems of limited commitment and limited liquidity. If a firm has to rely on relational contracts to motivate its workforce, and if it faces a volatile environment, investments into general, non-relationship-specific, capital can increase the efficiency of a firmś labor relations.
Keywords: C73; D21; D86; G32; 330; relational contracts; corporate finance; capital investments